Overview of experimental investigations of X-ray radiation generated by 500-800 MeV electrons in multicrystal and multilayer radiators carried out at Tomsk synchrotron; Journal of Physics: Conference Series; Vol. 517, iss. 1 : RREPS-13. Radiation from Relativistic Electrons in Periodic Structures and Meghri-13. Electron, Positron, Neutron and X-ray Scattering under External Influences - Kaplin V. V. Valery Viktorovich; Kuznetsov S. I. Sergey Ivanovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich (2014, 2014)
Title screen